1970
DOI: 10.1536/ihj.11.74
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Identification of Variation Sources of Transthoracic Electrical Impedance during Breath Holding

Abstract: SUMMARYVariations of transthoracic electrical impedance and their relations with physiological events within the thorax were studied by using electrodes applying constant sinusoidal current at 55kHz on bilateral chest walls of anesthetized dogs during breath holding. The level of the impedance lowered during decrease of oxygen and elevated during ether gas evaporation in the lungs with steady pulmonary blood flow. The impedance decreased when concentrated saline was selectively infused into the pulmonary vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1973
1973
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
1
0
1
Order By: Relevance
“…Nyboer entitled his seminal 1940 paper, ‘The impedance plethysmograph: an electrical volume recorder’ (Nyboer & Hamilton, 1940). His successors, Kubicek (Kubicek et al 1974), Bonjer (Bonjer et al 1952), Hukushima (Hukushima, 1970), Lababidi (Lababidi et al 1970), Patterson (Patterson et al 1978) and ourselves, have begun with the assumption that thoracic impedance is fundamentally and inversely related to the volume of blood in the thorax. In turn, we and others have concluded that most of the changes in conductance are due to changes in the volume of the thoracic aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Nyboer entitled his seminal 1940 paper, ‘The impedance plethysmograph: an electrical volume recorder’ (Nyboer & Hamilton, 1940). His successors, Kubicek (Kubicek et al 1974), Bonjer (Bonjer et al 1952), Hukushima (Hukushima, 1970), Lababidi (Lababidi et al 1970), Patterson (Patterson et al 1978) and ourselves, have begun with the assumption that thoracic impedance is fundamentally and inversely related to the volume of blood in the thorax. In turn, we and others have concluded that most of the changes in conductance are due to changes in the volume of the thoracic aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Γιαμετρήσεις πνευμόνων με μη αιματηρές μεθόδους υπάρχει ένας περιορισμένος αριθμός δημοσιεύσεων που έχουν περισσότερο εμπειρικό χαρακτήρα. Αυτό αποδίδεται στην ηλεκτρική, φυσιολογική και ανατομική ανομοιομορφία των ιστών καθώς και στη μεταβαλόμενη ηλεκτρική συνεισφορά του όγκου του κυκλοφορούντος αίματος στο θώρακα (Hukushima, 1970;Sova, 1970" Kira et al, 1970* Kawakami et al, 1972" Patterson et al, 1978' Sakamoto et al, 1979, Brown et al, 1985. θα πρέπει να τονισθεί ότι ει δικά στον τομέα της θεωρητικής ανάλυσης υπάρχουν ελάχιστες πληροφορίες.…”
Section: εισαγωγηunclassified